Augmented Lagrangian and Galerkin least‐squares methods for membrane contact. (26th February 2018) - Burman, Erik; Hansbo, Peter; Larson, Mats G.
Summary: In this paper, we propose a stabilized finite element method for the numerical solution of contact between a small deformation elastic membrane and a rigid obstacle. We limit ourselves to friction‐free contact, but the formulation is readily extendable to more complex situations.